HADITH NARRATORS’ BIOGRAPHIES AND THEIR ROLE IN THE RELIABILITY OF TRANSMISSION (Contemporary Journal of Social Science Review, 2025)
This research study concerns the center of the existential competence to consider the authenticity of Hadith transmission and investigate how documenting lives has been positioned as a key stone in Islamic scholarship. This research reviews the emergence of an elaborate narratology, recounting how it formed as a rigid query system that originated with verification of oral eyewitness narratives and matured into complex authentication mechanisms recorded in biographies drawn from canonical literature.The paper concerns itself with the interface between precedent and preservation, dealing with Hadith scholars' primary means of qualification for transmitters, beyond the key standards utilized to grade narrators; integrity, memory and time suitability. It Exposes How these mechanisms of authentication were not only employed to verify the Prophetic traditions, they also subsequent avenues for historical source criticism that prefigured modern historiographic methods. Using an interdisciplinary approach it contributes to the Hadith vs. Tradition debate and brings together voices of Islamic scholarship with contemporary academic critiques. It underscores the new developments in digital analysis that are changing how we evaluate narrators, while also supporting some of the more traditional methods that still remain applicable today. The outcome highlights the ongoing importance of biographical work for sustaining the integrity of Islamic intellectual history and its relevance in wider conversations about textual transmission and historical reliability.